The impact of age in the outcome of patients with advanced or recurrent cervical cancer after platinum-based chemotherapy - Kastritis, E.; Bamias, A.; Bozas, G.; Koutsoukou, V.; Voulgaris, Z.; Vlahos, G.; Rodolakis, A.; Gika, D.; Papadimitriou, C.; Dimopoulos, M.A. (Gynecologic Oncology, 2007)
Objectives.: Cervical cancer is a disease of middle-aged and elderly but still there are young women diagnosed with advanced disease that is incurable with local treatment and is treated with platinum-based combination chemotherapy. It is unknown whether these young patients have a poorer outcome compared to older patients or whether elderly patients have inferior outcome than younger patients when treated with combination chemotherapy. Methods.: We compared the outcome between young (< 35), elderly (> 70) and middle-aged (35-70) women who were treated with platinum-based combination chemotherapy for advanced, recurrent or persistent disease. Results.: Two hundred and eighteen patients were included in our database. The baseline clinical and disease characteristics were not different between age groups but anemia and thrombocytosis were more frequent in younger patients. Median survival for all patients was 13.4 (95%CI 11-15.8) months while survival of patients < 35 years of age was 9 months (95% CI 5.8-12), of patients older than 70 was 10 months (95% CI 6.9-13) of patients 35 to 70 years of age was 14.5 months (95% CI 11-18) (p = 0.004). Multiple factors were significant for survival in univariate analysis but only weight loss, pain score and relapse inside an irradiated filed were significant predictors of outcome in multivariate analysis. Conclusions.: Very young (< 35) and elderly (> 70) patients have a worse prognosis after treatment with combination chemotherapy for advanced or recurrent cervical cancer. Nevertheless, this difference is not significant when adjusted for other prognostic factors. © 2006 Elsevier Inc. All rights reserved.
Keywords: Advanced; Cervical cancer; Elderly; Paclitaxel; Platinum; relapse; Young